Calcium-sensing receptor-mediated NLRP3 inflammasome activation in rheumatoid arthritis and autoinflammation - Werner, Lina Emilia; Wagner, Ulf (Frontiers in Physiology, 2023)
The calcium-sensing receptor (CaSR) is expressed in many cell types – including immune cells and in particular circulating monocytes. Here, the receptor plays an important physiological role as a regulator of constitutive macropinocytosis. This review article provides an overview of the literature on the role of the calcium sensing receptor in the context of inflammatory processes. Special emphasis is laid upon the importance for monocytes in the context of rheumatoid arthritis. We have shown previously, that stimulation of the receptor by increased extracellular Ca2+ ([Ca2+]ex) triggers a pro-inflammatory response due to NLRP3 inflammasome assembly and interleukin (IL)-1β release. The underlying mechanism includes macropinocytosis of calciprotein particles (CPPs), which are taken up in a [Ca2+]ex-induced, CaSR dependent manner, and leads to strong IL-1β release. In rheumatoid arthritis (RA), this uptake and the resulting IL-1β release is significantly increased due to increased expression of the receptor. Moreover, increased [Ca2+]ex-induced CPP uptake and IL-1β release is associated with more active disease, while CaSR overexpression has been reported to be associated with cardiovascular complications of RA. Most importantly, however, in animal experiments with arthritic mice, increased local calcium concentrations are present, which in combination with release of fetuin-A from eroded bone could contribute to formation of CPPs. We propose, that increased [Ca2+]ex, CPPs and pro-inflammatory cytokines drive a vicious cycle of inflammation and bone destruction which in turn offers new potential therapeutic approaches.